Financial Performance and Market Performance as Determinants of Telecommunications Sector Stock Prices on The Indonesian Stock Exchange - Gisijanto, Hantoro Arief; Asri , Hendri Rahmayani (Review: Journal of Multidisciplinary in Social Sciences, 2024)
The capital market has an important role in a country's economy through economic functions and financial functions. The function of the economy is because of the market that brings together the capital provider and the party that needs funds. The function of finance is because the capital market provides expectations or expectations of obtaining returns for the investor according to the type of investment taken. The purpose of this study is to analyze the effect of Debt to Equity Ratio (DER), Return On Equity (ROE), Earning Per Share (EPS), and Price Earning Ratio (PER) on Stock Prices in the telecommunications sector of the Indonesia Stock Exchange (IDX) for the period 2015 – 2022. This study uses quantitative secondary data, analyzed using multiple linear regression. The data used in this study uses the financial ratios Debt to Equity Ratio, Return On Equity, Earning Per Share, and Price Earning Ratio and Stock Price in the telecommunications sector of the Indonesia Stock Exchange (IDX) for the period 2015 – 2022. The sampling method in this study is a non-probability sampling technique with a type of purposive sampling. The results of this study show that the variables Return On Equity, Earning Per Share, Price Earning Ratio have an effect on the Stock Price, while the Debt to Equity Ratio variable has no effect on the Stock Price. The variable that has the most dominant influence on stock prices is the Earning Per Share (EPS) variable.